Analisis praktik, dan tantangan manajemen risiko perbankan syariah: Tinjauan literatur - Vio M., Anggun Milania (Maliki Interdisciplinary Journal, 2024)
Risk management is an important aspect in maintaining the sustainability and success of financial institutions, including in the rapidly growing context of Islamic banking. This research uses the literature study method to explore risk management practices in Islamic banking, focusing on risk identification, evaluation, control and monitoring. Data were collected from various sources, including journals and books. The results show that risk management practices in Islamic banking are based on sharia principles, involving aspects such as financing, interest rate, liquidity, and operational risk management. Specific challenges include Shariah compliance in all aspects of operations, in-depth understanding of Shariah products, as well as integration with conventional financial markets. Future research is recommended to explore more specific risk management practices in Islamic banking and their relationship with financial performance.